Distinct role of the Fas rs1800682 and FasL rs763110 polymorphisms in determining the risk of breast cancer among Han Chinese women - Wang M; Wang Z; Wang XJ; Jin TB; Dai ZM; Kang HF; Guan HT; Ma XB; Liu XH; Dai ZJ (Dove Medical Press, 2016)
Meng Wang,1,* Zheng Wang,2,* Xi-Jing Wang,1 Tian-Bo Jin,3 Zhi-Ming Dai,4 Hua-Feng Kang,1 Hai-Tao Guan,1 Xiao-Bin Ma,1 Xing-Han Liu,1 Zhi-Jun Dai1 1Department of Oncology, Second Affiliated Hospital of Xi’an Jiaotong University, 2Department of Medical Oncology, Xi’an Central Hospital, 3National Engineering Research Center for Miniaturized Detection Systems, School of Life Sciences, Northwest University, 4Department of Anesthesia, Second Affiliated Hospital of Xi’an Jiaotong University, Xi’an, People’s Republic of China *These authors contributed equally to this work Background: In recent years, studies have demonstrated that polymorphisms in the promoters of Fas and FasL are significantly associated with breast cancer risk. However, the results of these studies were inconsistent. This case–control study was performed to explore the associations between Fas rs1800682 and FasL rs763110 polymorphisms and breast cancer. Materials and methods: A hospital-based case–control study of 560 Han Chinese females with breast cancer (583 controls) was conducted. The MassARRAY system was used to search for a possible association between the disease risk and the two single nucleotide polymorphisms, Fas rs1800682 and FasL rs763110. Statistical analyses were performed using SNPStats software to conduct Pearson’s chi-square tests in five different genetic models. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated after adjustment to age and body mass index. PHASE v2.1 software was used to reconstruct all common haplotypes.Results: A statistically significant association was found between Fas rs1800682 and increased breast cancer risk (AG vs AA: OR =1.37, 95% CI =1.06–1.78; AA+AG vs GG: OR =1.32, 95% CI =1.04–1.66), and also it was found that the FasL rs763110 polymorphism may decrease the risk. Stratified analyses demonstrated that the rs763110 polymorphism was associated with lower breast cancer risk among postmenopausal females (heterozygote model: OR =0.69, 95% CI =0.49–0.97; dominant model: OR =0.70, 95% CI =0.51–0.96). The T allele of rs763110 was also associated with a decreased risk of lymph node metastasis (allele model: OR =0.75, 95% CI =0.57–0.97) and an increased risk of the breast cancer being human epidermal growth factor receptor 2 positive (allele model: OR =1.37, 95% CI =1.03–1.18). Moreover, haplotype analysis showed that Ars1800682Trs763110 was associated to a statistically significant degree with lower risk of breast cancer (OR =0.70, 95% CI =0.53–0.91). Conclusion: These data suggest that the presence of Fas rs1800683 is an important risk factor for breast cancer, whereas FasL rs763110 may exert a protective effect against the onset of breast cancer. Keywords: Fas, FasL, single nucleotide polymorphism, breast cancer, risk